2021
DOI: 10.1136/archdischild-2020-321538
|View full text |Cite
|
Sign up to set email alerts
|

Automated control of oxygen titration in preterm infants on non-invasive respiratory support

Abstract: ObjectiveTo evaluate the performance of a rapidly responsive adaptive algorithm (VDL1.1) for automated oxygen control in preterm infants with respiratory insufficiency.DesignInterventional cross-over study of a 24-hour period of automated oxygen control compared with aggregated data from two flanking periods of manual control (12 hours each).SettingNeonatal intensive care unit.ParticipantsPreterm infants receiving non-invasive respiratory support and supplemental oxygen; median birth gestation 27 weeks (IQR 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
0
16
1
1
Order By: Relevance
“…In our study, the proportion of time spent in the hyperoxaemic range was lower in the A-Fio 2 arm, but this difference was not statistically significant. This is unlike the previous studies that have shown a statistically significant reduction in the hyperoxaemia 8–12 15 16. This may be due to the enhanced awareness among staff regarding the importance of the Spo 2 targeting in preterm infants 23.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In our study, the proportion of time spent in the hyperoxaemic range was lower in the A-Fio 2 arm, but this difference was not statistically significant. This is unlike the previous studies that have shown a statistically significant reduction in the hyperoxaemia 8–12 15 16. This may be due to the enhanced awareness among staff regarding the importance of the Spo 2 targeting in preterm infants 23.…”
Section: Discussioncontrasting
confidence: 73%
“…It is now possible to control the Fio 2 using automatic technology. Several studies have consistently shown that automatic oxygen control (A-Fio 2 ) improves compliance with Spo 2 targeting8–15 and reduces hypoxaemia11–13 15 16 and hyperoxaemia8–12 15 16 in preterm infants on respiratory support. However, the trials were of short duration.…”
Section: Introductionmentioning
confidence: 99%
“…It is often perceived at the bedside that FiO2 tends to be higher with A-FiO2 than M-FiO2. Some cross over studies with A-FiO2, did not show any statistical difference in the median FiO2 (32,36,42), was lower in A-FiO2 arm in Claure et al's study (31) and higher in Dijkman et al's study using PRICO (45).…”
Section: Average Fio2mentioning
confidence: 80%
“…The details of the currently available studies are shown in Table 1 (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Majority of these studies were cross-over RCT.…”
Section: Current Available Evidence For the Use Of A-fio2 In Neonatesmentioning
confidence: 99%
“…Questions remain regarding the scalability of this technology to the wider population and the need for large sample long-term follow-up studies ( 97 ), but equally, NAVA could represent an effective way of both measuring and responding to apnoeic events as they occur. Moreover, automated oxygen titration systems are beginning to be used in some NICUs following recent work highlighting their safety ( 100 ). The impact of these systems on AOP dynamics warrants investigation.…”
Section: Improvements In Aop Measurementmentioning
confidence: 99%